Protocol to detect neutral lipids with BODIPY staining in myeloid-derived suppressor cells in mouse mammary tumors - Ukjin Kim; Rumela Chakrabarti (STAR Protocols)
Summary: Neutral lipids affect the immunosuppressive function of myeloid-derived suppressor cells (MDSCs). Here, we present a protocol for measuring neutral lipids in MDSCs using BODIPY from mouse mammary tumor derived from triple-negative breast cancer cells, 4T1, which is applicable to other mammary tumors of interest. We describe steps for 4T1 cell culture, single-cell isolation from tumors, staining of cells with antibodies and BODIPY, and flow cytometry. Furthermore, we introduce alternative protocols with MDSC sorting to overcome risk of cell death by BODIPY.For complete details on the use and execution of this protocol, please refer to Kim et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.